2020
DOI: 10.1016/j.amjmed.2019.12.041
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Fitness Is Associated With Early Death Among Healthy Young and Middle-Aged Baby Boomers and Generation Xers

Abstract: had full access to all the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…At the same time, improve the physical condition of students. Therefore, a healthy physical fitness aerobics teaching is designed [ 9 , 10 ]. There are also researchers who experiment with middle school students, who always take “health first” as their guiding ideology [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, improve the physical condition of students. Therefore, a healthy physical fitness aerobics teaching is designed [ 9 , 10 ]. There are also researchers who experiment with middle school students, who always take “health first” as their guiding ideology [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heidi et al, reported that leisure-time physical activity was related to a lower risk of premature death in patients with CKD and type 1 diabetes [ 16 ]. Moreover, a U.S. Baby Boomers and Generation Xers study demonstrated that lower cardiorespiratory fitness during middle adulthood was inversely associated with premature death [ 15 ]. In addition, in a Swedish national cohort study of 1,547,478 military conscripts, muscle strength, aerobic fitness, and obesity were associated with a higher risk of mortality in adulthood [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to other diseases, premature death is the leading cause of death among the youngest and most productive age group and a leading cause of potential loss of lifespan [ 13 , 14 ]. In the general population and in those with type 1 diabetes, higher levels of physical activity or cardiorespiratory fitness are linked to a lower risk of premature death [ 15 , 16 , 17 ]. Lower level of handgrip strength has been found to be a predictor of death in the elderly in several investigations [ 1 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Participants were considered as having cancer by self-reported having ever been told by a physician that they had such conditions. Diabetes was defined by self-reporting having been told by a physician that they had diabetes or reporting currently taking insulin to treat diabetes [33].…”
Section: Chronic Conditionmentioning
confidence: 99%